Pengaruh media pembelajaran Puzzle terhadap Matematika - Sirait, Fitri Novita Sari; Panjaitan, Muktar B.; Thesalonika, Emelda (SUKMA: Jurnal Pendidikan, 2023)
AbstractThe problem in this study is that student learning outcomes are still less than optimal. This study aims to determine how much influence the Puzzle Learning Media has to improve student learning outcomes in the fourth grade mathematics subject UPTD SD Negeri 124405 Pematangsiantar. This type of research is a quantitative research conducted at UPTD SD Negeri 124405 Pematang Siantar, with a sample of 36 students. Data collection techniques using tests and documentation. And the data analysis technique used normality, homogeneity, t test and simple regression analysis. Hypothesis Testing with a significance level of 5%. The analysis in the early stages shows that the population is normally distributed, has the same variance, and has learning outcomes that are not optimal. When given the pre test, it is known that the average learning outcomes of the experimental class and control class are 50.00 and 36.18, after being given treatment then a post test is done, it is known that the average learning outcomes of the experimental class and control class are 91.58 and 52.06. So that the increase in the experimental class is 21.58 and the control class is 15.88. From the results obtained, there is a positive and significant influence between Puzzle Learning Media (X) To improve Learning Outcomes (Y) Mathematics for fourth grade students UPTD SD Negeri 124405 Pematang Siantar T.A 2022/2023 with a value of tcount> ttable (12.191> 2.032) and a value of Sig (2-tailed) 0.000 < 0.05. Based on the analysis of Key data, the puzzle learning media has a positive and significant effect on improving student learning outcomes in the fourth grade mathematics subject at UPTD SD Negeri 124405 Pematang Siantar T.A 2022/2023.